Hidden talents - Krentz, Jayne Ann; Copyright Paperback Collection (Library of Congress) (New York Pocket Books, 1993)
When opposites fall in love, they clash by daytime and explode at night
1
Keywords: Artist colonies -- Washington (State) -- Fiction; Washington (State) -- Fiction; Love stories